Odpowiedzi

2009-12-12T18:05:37+01:00
F) 12p-7r=-16
p-3r=-69 /+3r
12p-7r=-16
p=-69+3r
12(-69+3r)-7r=-16
p=-69+3r
-828+36r-7r=-16
p=-69+3r
-828+29r=-16 /+828
p=-69+3r
29r=812 / podzielone przez 29
p=-69+3r
r=28

p=-69+3(28)
p=15

3 3 3
2009-12-12T18:14:39+01:00
F) 12p-7r=-16
p-3r=-69
12p-7r= -16
p= -69+3r
12(-69+3r) - 7r=-16
p= -69+3r
-828 + 36r -7r=-16
p= -69+3r
29r = 812/:29
p= -69+3r
r=28
p= -69 +3*28
r=28
p=15
g)8a+9b=36
a-16b=210/*(-8)
8a+9b =36
-8a-72b= -288
-72b+9b=-288+36
-63b=-252/)-63)
b=4
8a+ 9*4=36
8a+36=36
8a=0/8
a=0

h)2x=2y=8
2x-3y=-7
2x=2y=8
2x=-7+3y
-7+3y=2y=8
2x=-7+3y
-7+3y-2y=8
2x=-7+3y
-7+y=8
2x=-7+3y
y=15
2x=-7+3*15
y=15
2x=-7+45
y=15
2x=38
y=15
x=19

i)4y+2x=10/*(-2)
3x+8y=10
-8y-4x= -20
3x+8y=10
x=-10
4y- 20=10
4y=30/4
y=7,5
j)4a+2b=10
5a-2b=-10
9a=0/9
a=0
2b=10
b=5

k)4(x-2)-(y-2)=1
10x-2y=18
4x-8-y+2=1
10x-2y=18
4x-y= 1+6/*(-2)
10x-2y=18
-8x+2y=-14
10x-2y=18
2x=4/2
x=2
4*2-y=7
8-y=7
-y=-1/*(-1)
y=1
2 5 2
2009-12-12T18:26:58+01:00
F) 12p-7r=-16
p-3r=-69

12p-7r=-16
p=-69-3r

12(-69-3r)-7r=16
p=-69-3r

-828-36r-7r=-16
p=-69-3r

-43r=812/-43
p=-69-3r

r=-18,9
p=-69-3*(-18,9)

r=-18,9
p=69-(-56,7)

r=-18,9
p=125,7



g)8a+9b=36
a-16b=210

8a+9b=36
a=9b+36

8(9b+36)+9b=36
a=9b+36

72b+288+9b=36
a=9b+36

81b=252/81
a=9b+36

b=3,1
a=9*3,1+36

b=3,1
a=63,9


h)2x+2y=8/2
2x-3y=-7

x=4-y
2(2-y)-3y=-7

x=4-y
4-2y-3y=-7

x=4-y
-5y=-11/(-5)

x=4-y
y=11/5

x=2 i 4/5
y=1 i 1/5


i)4y+2x=10
3x+8y=10

2x=10-4y/2
3x+8y=10

x=5-2y
3(5-2y)+8y=10

x=5-2y
15-6y+8y=10

x=5-2y
2y=-5/2

x=5-2y
y=-2,5

x=10
y=-2,5


j)4a+2b=10/2
5a-2b=-10

b=5-2a
5a-2(5-2a)=-10

b=5-2a
5a-10+4a=-10

b=5-2a
9a=0/9

b=5-2a
a=0

b=5
a=0


k)4(x-2)-(y-2)=1
10x-2y=18

4x-8-y+2=1
10x-2y=18/2

4x-6-y=1
y=8-5x

4x-6-8-5x=1
y=8-5x

-x=15
y=8-5x

x=-15
y=83